Rwanda : 2021 Article IV Consultation and Fifth Review Under the Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report, 2022)
Rwanda's medium-term outlook is positive, supported by the authorities' large policy package to respond to the evolving COVID-19 pandemic and their continued commitment to the PCI in a challenging environment. Economic recovery is underway with easing of restrictions supported by faster vaccination rates since July. GDP growth is projected at 10.2 percent in 2021 and inflation remained subdued. But Rwanda's remarkable economic and social progress over the last two decades faces a significant setback, with poverty, unemployment, and gender inequalities on the rise. These pandemic scars, if not addressed, risk reversing hard-won economic and social gains. With a large share of the population still unvaccinated and the emergence of new variants, risks to the outlook remain elevated.